Characteristic Depths, Fluxes, and Timescales for Greenland's Tidewater Glacier Fjords From Subglacial Discharge‐Driven Upwelling During Summer. Issue 10 (17th May 2022) - Slater, D. A.; Carroll, D.; Oliver, H.; Hopwood, M. J.; Straneo, F.; Wood, M.; Willis, J. K.; Morlighem, M.
Abstract: Greenland's glacial fjords are a key bottleneck in the earth system, regulating exchange of heat, freshwater and nutrients between the ice sheet and ocean and hosting societally important fisheries. We combine recent bathymetric, atmospheric, and oceanographic data with a buoyant plume model to show that summer subglacial discharge from 136 tidewater glaciers, amounting to 0.02 Sv of freshwater, drives 0.6–1.6 Sv of upwelling. Bathymetric analysis suggests that this is sufficient to renew most major fjords within a single summer, and that these fjords provide a path to the continental shelf that is deeper than 200 m for two‐thirds of the glaciers. Our study provides a first pan‐Greenland inventory of tidewater glacier fjords and quantifies regional and ice sheet‐wide upwelling fluxes. This analysis provides important context for site‐specific studies and is a step toward implementing fjord‐scale heat, freshwater and nutrient fluxes in large‐scale ice sheet and climate models. Plain Language Summary: The interaction between the Greenland Ice Sheet and the surrounding ocean is one of the key links in the regional climate system. Ocean heat melts the edges of the ice sheet, causing glacier speed‐up, retreat and sea level contribution. Meltwater from the ice sheet enters the ocean where it alters ocean properties and potentially ocean currents. This meltwater also drives upwelling of nutrients that can impact local ecosystems. All of these processes occur in long, deep and narrow fjords that connect the ice sheet and ocean. In this study, we present a first continent‐wide overview of the geometry and dynamics of Greenland's fjords. We combine recent bathymetric, atmospheric, and oceanographic datasets with a simple model to show that many fjords are well connected to the ocean in both bathymetry and circulation, suggesting that changes in the ocean on the continental shelf will be quickly transmitted to the ice sheet margin. We also suggest that meltwater from the ice sheet is rapidly mixed within fjords and will enter the wider ocean as a dilute subsurface mixture. This study is a step toward implementing fjord heat, freshwater and nutrient fluxes into large‐scale models that cannot resolve fjords. Key Points: We present a first ice sheet‐wide inventory of subglacial discharge‐driven upwelling plumes around the margin of the Greenland Ice Sheet Just 0.02 Sv of subglacial discharge drives 0.6–1.6 Sv of upwelling that settles at 0–260 m depth and can renew most fjords within a summer Fjords provide a path to the ocean deeper than 200 m for 82 out of 136 glaciers considered, suggesting warm waters reach most major glaciers